Neurosemiotyka jako hermeneutyka kultury i literatury (Krótki komentarz do rozpraw Jana Kordysa) - Balbus, Stanisław (Przestrzenie Teorii, 2007)
This sketch presents the most important linguistic and semiological premises of the relatively new field of science, neurosemiotics, which is the research base of Jan Kordys' studies, who transformed it into a neurosemiotical hermeneutics of culture-texts, as a branch of the modern philosophical anthropology.